Hansen's Disease The Forgotten and Neglected Disease - Ribòn, Wellman (IntechOpen, 2019)
Hansen's Disease - The Forgotten and Neglected Disease provides concise information on the relevant aspects of the disease of leprosy, including immunological, epidemiological, clinical and molecular studies that are of great importance in the study of an often-ignored disease, which remains a great challenge to humanity. It collects contributions made by professional experts in the study of Mycobacterium leprae, providing perspectives with knowledge, experience and research, highlighting that the disease continues to be of interest to public health. It is expected that this book will be useful and contribute to the expansion of information and interest about the disease commonly known as leprosy.